Analysis of isotope element by electrolytic enrichment method for ground water and surface water in Saurashtra region, Gujarat, India. Issue 1 (31st December 2016) - Singh, Sajal; Hussain, Athar; Khobragade, S.D.
Abstract: The present study has been aimed for the assessment of isotope element Tritium ( 3 H). It is a great threat to human health and environment for lengthy duration. The tritium exists in earth in diverse forms such as (1) small amounts of natural tritium are produced by alpha decay of lithium-7, (2) natural atmospheric tritium is also generated by secondary neutron cosmic ray bombardment of nitrogen, (3) atmospheric nuclear bomb testing in the 1950s, although the contribution from nuclear power plants is small. Tritium or 3 H is a radioactive isotope of hydrogen with a half-life of 12.32 ± 0.02 years. Water samples from ground water, surface water, and precipitation were collected from different locations in Gujarat area and were analyzed for the same. Distillation of samples was done to reduce the conductivity. Deuterium and Hydrogen were removed by the process of physico-chemical fractionation in the tritium enrichment unit. The basis of physico-chemical fractionation is the difference in the strength of bonds formed by the light vs. the heavier isotope of a given element. A total of 10 cycles (runs) were executed using Quintals process. Tritium concentration files were created with help of WinQ and Quick start software in Quintals process (Liquid Scintillation Spectrometer). The concentration of tritium in terms of tritium units (TU) of various samples has been determined. The TU values of the samples vary in the range of 0.90–6.62 TU.